2020
DOI: 10.1515/dmpt-2019-0021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tramadol pharmacokinetics in correlation with CYP2D6 and clinical symptoms

Abstract: Objectives Due to lack of adequate data on tramadol kinetic in relevance of CYP2D6 toxicity, this study was designed to investigate the effect of CYP2D6 phenotype in tramadol poisoning. The saliva, urine and blood samples were taken at the admission time. Consequently, concentration of tramadol and its major metabolites were measured. Methods A pharmacokinetic and metabolic study was developed in cases of tramadol poisoned (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Our findings also revealed that seizures were more common in men than in women. This finding can be found in most studies (5,9,12,19,20). Regardless of physiological differences between sexes, differences in the amount or duration of consumption between sexes may influence the occurrence of this finding, as some studies show that seizures are directly related to tramadol dosage (5,14).…”
Section: Discussionmentioning
confidence: 80%
“…Our findings also revealed that seizures were more common in men than in women. This finding can be found in most studies (5,9,12,19,20). Regardless of physiological differences between sexes, differences in the amount or duration of consumption between sexes may influence the occurrence of this finding, as some studies show that seizures are directly related to tramadol dosage (5,14).…”
Section: Discussionmentioning
confidence: 80%